HEALTH PROFESSIONALS AND BLOOD PRESSURE MEASUREMENT: SCOPING REVIEW AND PROTOCOL FOR KNOWLEDGE, PERCEPTION AND PRACTICE. (June 2018) - Todkar, S.; Padwal, R.; Cloutier, L.
Abstract : Objective: Blood pressure measurement (BPM) is a fundamental aspect of hypertension management. Guidelines regarding BPM methods namely home (HBPM), ambulatory (ABPM), office (OBPM) and automated (AOBP) are strongly recommended and supported by Hypertension Canada guidelines. Since health professionals (HP) play an important role in BPM and hypertension management a clearer picture of the knowledge, perception and practices of HP is needed. A scoping review was conducted to identify all studies assessing knowledge, perception and practices of HP with regard to all BPM methods. Design and method: Keywords were identified and extraction was completed using the CINAHL and MEDLINE databases. A total of 74 potentially relevant studies were identified for scoping review. Results: Of the 74 studies identified, 16 studies focused on HBPM, 7 studies focused on ABPM, 5 studies focused on AOBP, 46 studies focused on OBPM. Majority of studies enrolled physicians, whereas few studies enrolled nurses. The results presented focused on knowledge, perception and practices. As for knowledge, studies on HBPM (5), AOBP (1) OBPM (17) demonstrated lack of agreement among HP with regard to BPM techniques. No Canadian study assessed the knowledge of HP with regard to BPM techniques. As for perception, majority of studies on HBPM (7), ABPM (3), AOBP (1), OBPM (3) showed positive perceptions towards the usefulness of BPM methods in clinical practice. As for practice, the majority of studies on ABPM (4), AOBP (4), OBPM (21) showed unsatisfactory practices among HP with regard to BPM techniques. Lack of knowledge, less positive perceptions and unsatisfactory practices were observed in studies performed in USA, Canada, UK, Europe, and Asia. Conclusions: Knowledge, perception and good practices are essential components of accurate BPM. The present scoping review therefore suggests the need to identify the gap between recommended guidelines and actual knowledge, perception and practices in primary care. A proposed protocol will include descriptive survey with an online questionnaire. Items in the questionnaire will distinctly focus on knowledge, perception and practices of HP with regard to BPM methods. This questionnaire will be developed in accordance with the guidelines.